Evaluation of the disciplinary competences of the students of the Bachelor's degree in Nursing at 'Sapienza' University of Rome through the TECO: a cross-sectional study. (30th October 2020) - Sansoni, Julita; Farina, Ilaria; Paterniani, Albina; Tofani, Marco; Galeoto, Giovanni
The objective of the study is to evaluate whether the TECO-D is a useful tool for measuring the skills acquired by students during three years of the nursing bachelor's degree course at the 'Sapienza' University of Rome. The sample was recruited between January and April 2018. The distribution of the scores for the TECO-D shows an increasing average (standard deviation) from 177.3 ± 28 in the first year up to 214.1 ± 18.5 for graduating students. The test is comprehensive by sampling all relevant disciplines in a curriculum, usually determined by a fixed blueprint. The evaluation of the single macro areas showed statistically significant data reflecting increasing knowledge regarding the progression of the skills. Because of this, we can say that the TECO-D is a great tool for determining student's knowledge in order to evaluate study programs.